A methodology for flexibility analysis of process piping. (December 2018) - Zahid, Umer; Khan, Sohaib Z; Khan, Muhammad A; Bukhari, Hassan J; Ahmed, Imran; Khan, Kamran A
Design of piping system requires a systematic consideration of various factors as addressed by the codes and standards. This research paper aims to provide a method for flexibility analysis of a selected area of process piping at an industrial plant. Analysis is done for the purpose of accommodating a spare heat exchanger in the process layout. The analysis follows a systematic procedure, with preparation of a tentative model of the system on CAESAR II software followed by insertion of different pipe supports. The selection and location of these supports is based on the results obtained from displacement, stress, reaction and equipment nozzle analysis of the piping system. The design is in accordance with ASME B31.3, which is the standard code for process piping. The proposed method can be adapted for piping configuration of any industrial plant. With the provision of a systematic procedure, the method ensures time saving and efficient flexibility analysis of any piping system.